Adhesive composition for high-draw lithium battery aluminum-plastic film and preparation method thereof
By adding a composition of specific components to the adhesive for aluminum-plastic film of lithium batteries, the problem of poor performance of existing adhesives in deep-drain and high-temperature environments is solved, and the effects of high flexibility, deep-drain resistance and good heat resistance are achieved.
Patent Information
- Application Number
- CN202411913536.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-08
AI Technical Summary
The adhesives for aluminum-plastic films for existing lithium batteries do not have enough bonding ability and flexibility in actual use, especially in deep-drain and high-temperature environments.
A high-thickness lithium battery aluminum-plastic film adhesive composition is used, including polyester resin, modified epoxy resin, castor oil modified polyester polyol, neopentyl glycol, coupling agent, reactive diluent and hexamethylene diisocyanate curing agent, to form a high-performance adhesive through the interaction of these components.
It significantly improves the flexibility, deep-drain resistance and bonding strength of the adhesive, and has good heat resistance and moisture resistance, and is suitable for aluminum-plastic films of lithium batteries.
Smart Images

Figure BDA0005206319470000071 
Figure BDA0005206319470000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium batteries, and in particular to an adhesive composition for high-draw-depth lithium battery aluminum-plastic film and a preparation method thereof. Background Art
[0002] Aluminum-plastic film is a very important component material in soft-pack lithium batteries in the field of lithium battery materials. From the outside to the inside, the aluminum-plastic film is composed of a nylon layer, a glue layer, an aluminum film, a glue layer, and an inner lining layer. In such a structure, the adhesive ability and heat resistance of the glue layer are crucial to improving the overall performance of the aluminum-plastic film. In recent years, the deep-drawing resistance of aluminum-plastic film has also received attention and research and development. Chinese patent CN109679567B discloses a deep-drawing resistant two-component adhesive for lithium battery aluminum-plastic film, and the raw materials for preparation include a main agent and a curing agent, wherein the main agent includes 5-20 parts of polyester resin, 3-9 parts of nitrogen-modified phenolic epoxy resin, 3-9 parts of modified epoxy resin, 1-5 parts of polyether polyol, 1-5 parts of polyol, 0.1-0.5 parts of auxiliary agent and 52-80 parts of solvent. The adhesive obtained by this patent has good deep-drawing resistance, but the bonding ability and flexibility of the adhesive obtained by this patent need to be improved, especially when the adhesive is actually used in the aluminum-plastic film of lithium batteries, stronger bonding ability and deep-drawing resistance are required. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present application provides an adhesive composition for a high-drawing deep lithium battery aluminum-plastic film and a preparation method thereof. The adhesive composition for a high-drawing deep lithium battery aluminum-plastic film prepared in the present application has excellent flexibility, deep-drawing resistance and bonding strength. It also exhibits good heat resistance and moisture-proof effect, and is suitable for use in lithium battery aluminum-plastic films.
[0004] In the first aspect, the present application provides an adhesive composition for a high-draw depth lithium battery aluminum-plastic film, which adopts the following technical solution: An adhesive composition for high-draw lithium battery aluminum-plastic film comprises the following preparation raw materials, measured by mass: 15-20 parts of polyester resin, 10-12 parts of modified epoxy resin, 3-4 parts of castor oil-modified polyester polyol, 2-3 parts of neopentyl glycol, 0.5-0.8 parts of coupling agent, 6-8 parts of active diluent, 60-65 parts of solvent and 10-15 parts of hexamethylene diisocyanate curing agent.
[0005] By adopting the above technical scheme, polyester resin: as the main film-forming material, the basic performance of the adhesive is provided. Its structure contains methylene, and due to the influence of the special functional group (dicarbonyl strong electron-withdrawing group) in the resin, the hydrogen activity on the adjacent methylene is high, and it can undergo a ring-opening reaction with the modified epoxy resin under the catalysis of a catalyst, and the whole reaction process has no small molecule production and no polar functional group production, and there is no easily hydrolyzed group such as urethane bond and ether bond in its cross-linked product, and the wet heat resistance is excellent: the presence of the aforementioned active methylene can react quickly with the modified epoxy resin to form a cross-linked network structure, and the reaction speed is fast, which improves production efficiency. Modified epoxy resin: used to improve the heat resistance and flexibility of the adhesive. By adding modified epoxy resin, the heat-resistant stratification problem of the adhesive composition can be solved, and the flexibility of the adhesive composition can be significantly improved. Castor oil modified polyester polyol: can significantly improve the bonding strength and flexibility of the adhesive composition, and then improve the deep drawing ability of the adhesive composition, and the deep drawing can reach more than 18mm. Neopentyl glycol: can significantly improve the flexibility of the adhesive composition. Coupling agent: used to enhance the adhesion between the adhesive and the substrate. Reactive diluent: used to reduce the viscosity of the adhesive and improve its fluidity and permeability. Hexamethylene diisocyanate curing agent: used as a cross-linking agent, it can promote the curing process of the adhesive. In summary, the adhesive composition for high-deep-drawing lithium battery aluminum-plastic film prepared in this application has excellent flexibility, deep-drawing resistance and bonding strength. It also shows good heat resistance and moisture-proof effect, and is suitable for lithium battery aluminum-plastic film. Preferably, the preparation method of the polyester resin comprises mixing 0.2 mol of suberic acid, 0.45 mol of 1,4-butanediol and 2-2.5 g of a catalyst at 120-130° C. and reacting for 30-40 minutes, then adding 0.4 mol of methyl acetoacetate and 0.2 mol of dibutyl malonate and stirring evenly, heating to 140-150° C. and reacting for 30-40 minutes to obtain the polyester resin.
[0006] By adopting the above technical scheme, the structure of the prepared polyester resin contains methylene groups. Due to the influence of the special functional group (dicarbonyl strong electron-withdrawing group) in the resin, the hydrogen activity on the adjacent methylene groups is relatively high. This high activity enables the polyester resin to undergo a ring-opening reaction with the modified epoxy resin under the catalysis of a catalyst to form a cross-linked network structure. The entire reaction process does not produce small molecules or polar functional groups, and the cross-linked reaction product does not contain easily hydrolyzed groups such as urethane bonds and ether bonds, so it has excellent resistance to moisture and heat. The presence of the aforementioned active methylene group can react quickly with the modified epoxy resin to form a cross-linked network structure, and the fast reaction speed improves production efficiency.
[0007] Preferably, the catalyst is at least one of dioctyltin oxide and dibutyltin oxide.
[0008] Preferably, the preparation method of the modified epoxy resin comprises the following steps: S41, according to the mass fractions, add phenol, xylene formaldehyde resin and toluene solvent into the reactor and stir until fully dissolved, fill with nitrogen and heat to 160-170°C, add monobutyl tin triisooctanoate and continue to reflux for 2-3h until the water is removed, to obtain modified xylene formaldehyde resin; S42. According to the mass fraction, the reaction temperature is lowered to below 95°C, N'-dimethylurea is added, and the temperature is raised to the reflux temperature. After the reflux becomes clear, tri(2,3-epoxypropyl)isocyanurate and acetone are added to react for 3-5 hours. After the acetone is removed by rotary evaporation, a modified epoxy resin is obtained.
[0009] By adopting the above technical scheme, the prepared modified epoxy resin can solve the problem of heat-resistant delamination of the adhesive composition and significantly improve the heat resistance of the adhesive composition. This is very important for the stability and safety of the aluminum-plastic film of lithium batteries in high temperature environments. The addition of modified epoxy resin significantly improves the flexibility of the adhesive composition. This is particularly important for the performance of the aluminum-plastic film of lithium batteries in the deep drawing process, and can ensure that the aluminum-plastic film does not break or delaminate when bent or folded. The modified epoxy resin works together with other components to improve the bonding strength of the adhesive composition. This is very important to ensure the close bonding and good electrical connection between the aluminum-plastic film of lithium batteries and battery components. The active methylene in the modified epoxy resin and the polyester resin can react quickly to form a cross-linked network structure, which improves the production efficiency. This is of great significance for the large-scale production of aluminum-plastic films for lithium batteries. The use of modified epoxy resin improves the moisture and heat resistance of the adhesive composition. This is of great significance to ensure that the aluminum-plastic film of lithium batteries does not degrade or fail in a humid environment. In summary, modified epoxy resin plays a key role in the preparation of adhesive compositions for high-draw lithium battery aluminum-plastic films, which not only improves product performance, but also speeds up production efficiency and ensures product quality and reliability.
[0010] Preferably, the mass ratio of the phenol, xylene formaldehyde resin, toluene, monobutyltin triisooctoate, N'-dimethylurea, tri(2,3-epoxypropyl)isocyanurate and acetone is 100:240:500-550:0.1-0.2:0.2-0.3:147:250-270.
[0011] Preferably, the method for preparing the castor oil-modified polyester polyol comprises the following steps: S61. Add neopentyl glycol and castor oil into a reactor according to their mass fractions, mix and stir, add tetrabutyl titanate under nitrogen protection, raise the temperature to 210° C., maintain the temperature for reaction for 2-3 hours, and obtain product A; S62, according to the mass fraction, cool the product A to 125°C, add adipic acid under nitrogen protection, slowly heat to 190-200°C, maintain the temperature for 4-6 hours; after the reaction is completed, cool to room temperature to obtain product B; S63. Add triethylamine to product B according to mass fractions, and react at room temperature for 10-20 minutes to obtain castor oil-modified polyester polyol.
[0012] By adopting the above technical scheme, step S61: neopentyl glycol and castor oil are added to the reactor by mass fraction, mixed and stirred. Under nitrogen protection, tetrabutyl titanate is added as a catalyst, the temperature is raised to 210°C, and the temperature is maintained for reaction for 2-3 hours to obtain product A. The purpose of this step is to cause neopentyl glycol and castor oil to undergo a preliminary polymerization reaction to form a base polymer through high temperature reaction. Step S62: Cool product A to 125°C, add adipic acid under nitrogen protection, slowly heat to 190-200°C, and maintain the temperature for reaction for 4-6 hours. After the reaction is completed, cool to room temperature to obtain product B. The purpose of this step is to introduce adipic acid as a cross-linking agent through further polymerization reaction to increase the molecular weight and cross-linked network structure of the polymer. Step S63: triethylamine is added to product B by mass fraction, and reacted at room temperature for 10-20 minutes to obtain sesame oil-modified polyester polyol. The purpose of this step is to further adjust the structure of the polymer and optimize its performance through the action of triethylamine. The prepared castor oil modified polyester polyol can significantly improve the bonding strength and flexibility of the adhesive composition. This is because castor oil, as a natural oil, has good flexibility and adhesion, and these properties can be further improved after modification. Due to the presence of castor oil modified polyester polyol, the deep drawing ability of the adhesive composition has been significantly improved, and the deep drawing can reach more than 18mm. This is particularly important for the application of lithium battery aluminum plastic film, because the deep drawing ability directly affects the safety performance and service life of the battery. In summary, castor oil modified polyester polyol plays a key role in this application, not only improving the bonding strength and flexibility of the adhesive composition, but also enhancing its deep drawing ability, thereby making the adhesive composition more suitable for the application of lithium battery aluminum plastic film.
[0013] Preferably, the mass ratio of castor oil, neopentyl glycol, tetrabutyl titanate, adipic acid and triethylamine is 90-100:20-23:0.05-0.1:6-8:0.1-0.3.
[0014] Preferably, the coupling agent is composed of dodecyltrimethoxysilane, octyltrimethoxysilane and anilinemethyltriethoxysilane in a mass ratio of 3:2:1-3.
[0015] By adopting the above technical scheme, the role of the coupling agent in the adhesive composition is mainly to enhance the bonding strength and stability between materials. Dodecyltrimethoxysilane: It can react with hydroxyl groups or other active groups on the surface of the material to form chemical bonds, thereby improving the bonding strength of the material. At the same time, it can also form a cross-linked structure with other substances such as epoxy resin to improve the mechanical properties and heat resistance of the material. Octyltrimethoxysilane: This substance has good adhesion and flexibility, and can improve the flexibility and weather resistance of the adhesive composition. At the same time, it can also form a good bonding effect with a variety of materials. Anilinemethyltriethoxysilane: This substance is usually used to improve the bonding performance and heat resistance of materials. It can form chemical bonds with a variety of materials to improve the bonding strength and heat resistance of materials. The mass fraction ratio of these three substances is 3:2:1-3, which means that they can adjust the ratio according to specific needs to achieve the best bonding effect and material performance. This combination can provide an adhesive composition with excellent comprehensive performance, which is suitable for the production of high-depth lithium battery aluminum-plastic film. At the same time, the use of this coupling agent can also improve production efficiency and product quality.
[0016] Preferably, the active diluent is butyl glycidyl ether, and the solvent is butanone.
[0017] In a second aspect, the present application provides a method for preparing an adhesive composition for a high-draw depth lithium battery aluminum-plastic film, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned adhesive composition for high-draw depth lithium battery aluminum-plastic film, comprising the following steps: S101, adding one-half of the solvent and active diluent into a reaction kettle according to the mass fraction, heating to 50-55° C. and stirring, adding polyester resin, modified epoxy resin, castor oil-modified polyester polyol and neopentyl glycol to completely dissolve; then adding coupling agent, stirring and aging, adjusting the solid content and then discharging; obtaining a mixture; S102, adding hexamethylene diisocyanate curing agent to the remaining solvent for dilution, stirring evenly, and then adding it to the mixture, stirring evenly, to obtain an adhesive composition for high-draw depth lithium battery aluminum-plastic film.
[0018] In summary, the present application includes at least one of the following beneficial technical effects: 1. Flexibility and deep-drawing resistance: By adding castor oil-modified polyester polyol, the bonding strength and flexibility of the adhesive composition are significantly improved, so that it has excellent deep-drawing ability, which can reach more than 18 mm.
[0019] 2. Bonding strength: Also thanks to the application of castor oil-modified polyester polyol, the adhesive ensures sufficient bonding strength while maintaining flexibility, which is crucial for the long-term and stable use of lithium battery aluminum-plastic film.
[0020] 3. Heat resistance: By adding modified epoxy resin, the adhesive composition effectively solves the problem of heat-resistant delamination and significantly improves the overall heat resistance.
[0021] 4. Moisture-proof effect: The special functional groups (such as dicarbonyl) in the polyester resin make it possible for the cross-linked product generated when it reacts with the modified epoxy resin to contain no easily hydrolyzed groups, such as urethane bonds and ether bonds, thereby giving the adhesive composition excellent moisture and heat resistance.
[0022] 5. Reaction speed and production efficiency: The active methylene group in the polyester resin can quickly undergo a ring-opening reaction with the modified epoxy resin under the action of a catalyst, and no small molecule by-products or polar functional groups will be produced during the entire process. This not only increases the reaction speed, but also simplifies the production process, helping to improve production efficiency. DETAILED DESCRIPTION
[0023] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0024] In the following examples and preparation examples, 1 part means 100 g.
[0025] Preparation Example 1 Preparation of polyester resin The preparation method of polyester resin comprises the following steps: 0.2 mol of suberic acid, 0.45 mol of 1,4-butanediol and 2.3 g of dioctyltin oxide are mixed at 125° C. and reacted for 35 minutes, 0.4 mol of methyl acetoacetate and 0.2 mol of dibutyl malonate are added and stirred evenly, and the mixture is heated to 145° C. and reacted for 35 minutes to obtain polyester resin.
[0026] Preparation Example 2 Preparation of modified epoxy resin The preparation method of modified epoxy resin comprises the following steps: S41, according to the mass parts, add 100 parts of phenol, 240 parts of xylene formaldehyde resin and 530 parts of toluene solvent into the reactor and stir until fully dissolved, fill with nitrogen and heat to 165°C, add 0.15 parts of monobutyl tin triisooctanoate and continue to reflux for 2.3 hours until the moisture is gone, to obtain modified xylene formaldehyde resin; S42. According to the mass fraction, the reaction temperature was lowered to 93°C, 0.25 parts of N'-dimethylurea were added, and the temperature was raised to the reflux temperature. After the reflux became clear, 147 parts of tri(2,3-epoxypropyl)isocyanurate and 260 parts of acetone were added to react for 4 hours. After the acetone was removed by rotary evaporation, a modified epoxy resin was obtained.
[0027] Preparation Example 3 Preparation of castor oil modified polyester polyol The preparation method of castor oil modified polyester polyol comprises the following steps: S61. According to the mass fractions, 22 parts of neopentyl glycol and 98 parts of castor oil were added into a reactor, mixed and stirred, and under nitrogen protection, 0.07 parts of tetrabutyl titanate were added, and the temperature was raised to 210° C. and the temperature was maintained for 2.5 hours to obtain product A. S62, according to the mass fraction, cool the product A to 125°C, add 7 parts of adipic acid under nitrogen protection, slowly raise the temperature to 195°C, and keep the temperature for reaction for 5 hours; after the reaction is completed, cool to room temperature to obtain product B; S63. Add 0.2 parts of triethylamine to product B according to mass fractions, and react at room temperature for 15 minutes to obtain castor oil-modified polyester polyol.
[0028] Example 1 An adhesive composition for high-draw lithium battery aluminum-plastic film comprises the following raw materials, measured by mass: 15 parts of polyester resin, 10 parts of modified epoxy resin, 3 parts of castor oil-modified polyester polyol, 2 parts of neopentyl glycol, 0.5 parts of coupling agent, 6 parts of butyl glycidyl ether, 60 parts of solvent, and 10 parts of hexamethylene diisocyanate curing agent, wherein the coupling agent is composed of dodecyltrimethoxysilane, octyltrimethoxysilane and anilinemethyltriethoxysilane in a mass ratio of 3:2:1.
[0029] The method for preparing the adhesive composition for the high-draw-depth lithium battery aluminum-plastic film comprises the following steps: S101, according to the mass fractions, add one half of butanone and butyl glycidyl ether into a reaction kettle, heat to 50° C. and stir, add polyester resin, modified epoxy resin, castor oil-modified polyester polyol and neopentyl glycol and completely dissolve; then add a coupling agent, stir and ripen, adjust the solid content and then discharge; obtain a mixture; S102, adding hexamethylene diisocyanate curing agent to the remaining butanone to dilute it, stirring it evenly, and then adding it to the mixture, stirring it evenly, to obtain an adhesive composition for high-draw depth lithium battery aluminum-plastic film.
[0030] Example 2 An adhesive composition for high-draw lithium battery aluminum-plastic film comprises the following raw materials, measured by weight: 20 parts of polyester resin, 12 parts of modified epoxy resin, 4 parts of castor oil-modified polyester polyol, 3 parts of neopentyl glycol, 0.8 parts of coupling agent, 8 parts of butyl glycidyl ether, 65 parts of solvent, and 15 parts of hexamethylene diisocyanate curing agent, wherein the coupling agent is composed of dodecyltrimethoxysilane, octyltrimethoxysilane and anilinemethyltriethoxysilane in a weight ratio of 3:2:3.
[0031] The method for preparing the adhesive composition for the high-draw-depth lithium battery aluminum-plastic film comprises the following steps: S101. Add one-half of butanone and butyl glycidyl ether into a reaction kettle according to their mass fractions, heat to 55° C. and stir, add polyester resin, modified epoxy resin, castor oil-modified polyester polyol and neopentyl glycol and completely dissolve them; then add a coupling agent, stir and ripen, adjust the solid content and then discharge; obtain a mixture; S102, adding hexamethylene diisocyanate curing agent to the remaining butanone to dilute it, stirring it evenly, and then adding it to the mixture, stirring it evenly, to obtain an adhesive composition for high-draw depth lithium battery aluminum-plastic film.
[0032] Example 3 An adhesive composition for high-draw lithium battery aluminum-plastic film comprises the following raw materials, measured by mass: 18 parts of polyester resin, 11 parts of modified epoxy resin, 3.5 parts of castor oil-modified polyester polyol, 2.5 parts of neopentyl glycol, 0.7 parts of coupling agent, 7 parts of butyl glycidyl ether, 63 parts of solvent, and 12 parts of hexamethylene diisocyanate curing agent, wherein the coupling agent is composed of dodecyltrimethoxysilane, octyltrimethoxysilane and anilinemethyltriethoxysilane in a mass ratio of 3:2:2.
[0033] The method for preparing the adhesive composition for the high-draw-depth lithium battery aluminum-plastic film comprises the following steps: S101. Add one-half of butanone and butyl glycidyl ether into a reaction kettle according to their mass fractions, heat to 53° C. and stir, add polyester resin, modified epoxy resin, castor oil-modified polyester polyol and neopentyl glycol and completely dissolve them; then add a coupling agent, stir and ripen, adjust the solid content and then discharge; obtain a mixture; S102, adding hexamethylene diisocyanate curing agent to the remaining butanone to dilute it, stirring it evenly, and then adding it to the mixture, stirring it evenly, to obtain an adhesive composition for high-draw depth lithium battery aluminum-plastic film.
[0034] Comparative Example 1 The same as Example 3, except that: 29 parts of polyester resin and 0 parts of modified epoxy resin.
[0035] Comparative Example 2 The same as Example 3, except that: 0 parts of castor oil-modified polyester polyol and 6 parts of neopentyl glycol.
[0036] Comparative Example 3 The same as Example 3, except that: the coupling agent is dodecyltrimethoxysilane.
[0037] Comparative Example 4 The same as Example 3, except that the coupling agent is octyltrimethoxysilane.
[0038] Comparative Example 5 The same as Example 3, except that: the coupling agent is anilinemethyltriethoxysilane.
[0039] Performance testing The adhesive composition for high-draw lithium battery aluminum-plastic film prepared in the above Examples 1 to 3 and Comparative Examples 1 to 5 was sampled, coated on both sides of the aluminum foil, and baked in an oven at 80°C for 15 minutes. After drying, the thickness of the adhesive layer was about 6 microns. Then, the inner polypropylene layer and the outer nylon layer were bonded and aged, and the following tests were performed. The results are shown in Table 1.
[0040] Peel strength (per GB / T 8808-1988 "Peel test method for soft composite plastic materials"): the sample width is a long strip of 15mm, and the test speed is 100mm / min; High temperature peeling test: refer to the peeling strength test method and test the specimen at 120℃; Deep punching performance test: Use a double-pit deep punching die with a distance of 1mm between the two pits, punch at different depths, and observe whether there are abnormal phenomena such as delamination and whitening at the edges and corners of the outer film after deep punching. The maximum depth of delamination and whitening is the deep punching depth; Heat resistance test (put the sample into a 180℃ oven after punching to a depth of 7.5mm for heat resistance test, take out the sample after 20S to observe whether bubbling / delamination of the aluminum foil occurs); Double 85 moisture and heat resistance (GB / T 2423.50 (1000h), moisture and heat aging resistance: After punching 7.5mm, place the sample in a constant temperature and humidity chamber at a temperature of 85℃ and a relative humidity of 85% for 1000h, and check the appearance of the sample to see if the aluminum foil has bubbling / delamination.
[0041] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The adhesive composition for high-deep-drawing lithium battery aluminum-plastic film prepared in Examples 1 to 3 has excellent flexibility, deep-drawing resistance and bonding strength. It also exhibits good heat resistance and moisture-proof effect, and is suitable for lithium battery aluminum-plastic film.
[0042] 2) The performance comparison analysis of the adhesive composition for the high-drawing deep-drawing lithium battery aluminum-plastic film prepared in Example 3 and Comparative Example 1 shows that the modified epoxy resin prepared by the present application can solve the problem of heat-resistant delamination of the adhesive composition and significantly improve the heat resistance of the adhesive composition. This is crucial for the stability and safety of the aluminum-plastic film of lithium batteries in high temperature environments. The addition of the modified epoxy resin significantly improves the flexibility of the adhesive composition. This is particularly important for the performance of the aluminum-plastic film of lithium batteries in the deep-drawing process, and can ensure that the aluminum-plastic film does not break or delaminate when bent or folded. The modified epoxy resin works together with other components to improve the bonding strength of the adhesive composition. This is crucial to ensure the close bonding and good electrical connection between the aluminum-plastic film of lithium batteries and the battery assembly. The active methylene in the modified epoxy resin and the polyester resin can react quickly to form a cross-linked network structure, thereby improving production efficiency. This is of great significance for the large-scale production of aluminum-plastic films for lithium batteries. The use of the modified epoxy resin improves the moisture and heat resistance of the adhesive composition. This is of great significance for ensuring that the aluminum-plastic film of lithium batteries does not degrade or fail in a humid environment.
[0043] 3) The performance comparison analysis of the adhesive composition for high-drawing deep lithium battery aluminum-plastic film prepared in Example 3 and Comparative Example 2 shows that the addition of castor oil-modified polyester polyol prepared in this application can significantly improve the bonding strength and flexibility of the adhesive composition. This is because castor oil, as a natural oil, has good flexibility and adhesion, and these properties can be further improved after modification. Due to the presence of castor oil-modified polyester polyol, the deep drawing ability of the adhesive composition has been significantly improved, and the deep drawing can reach more than 18mm. This is particularly important for the application of lithium battery aluminum-plastic film, because the deep drawing ability directly affects the safety performance and service life of the battery.
[0044] 4) A comparative analysis of the performance of the adhesive composition for high-draw lithium battery aluminum-plastic film prepared in Example 3 and Comparative Examples 3 to 5 shows that the coupling agent is composed of dodecyltrimethoxysilane, octyltrimethoxysilane and anilinemethyltriethoxysilane in a mass ratio of 3:2:2, and the role of the coupling agent in the adhesive composition is mainly to enhance the bonding strength and stability between the materials. By utilizing their combined effect, the comprehensive performance of the adhesive composition can be significantly improved.
[0045] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. An adhesive composition for high-draw lithium battery aluminum-plastic film, characterized in that: The preparation raw materials include the following by weight: 15-20 parts of polyester resin, 10-12 parts of modified epoxy resin, 3-4 parts of castor oil modified polyester polyol, 2-3 parts of neopentyl glycol, 0.5-0.8 parts of coupling agent, 6-8 parts of active diluent, 60-65 parts of solvent and 10-15 parts of hexamethylene diisocyanate curing agent.
2. The adhesive composition for high-draw lithium battery aluminum-plastic film according to claim 1, characterized in that: The preparation method of the polyester resin comprises the following steps: 0.2 mol of suberic acid, 0.45 mol of 1,4-butanediol and 2-2.5 g of a catalyst are mixed at 120-130° C. for reaction for 30-40 minutes, 0.4 mol of methyl acetoacetate and 0.2 mol of dibutyl malonate are added and stirred evenly, and the mixture is heated to 140-150° C. for reaction for 30-40 minutes to obtain the polyester resin.
3. The adhesive composition for high-draw lithium battery aluminum-plastic film according to claim 2, characterized in that: The catalyst is at least one of dioctyltin oxide and dibutyltin oxide.
4. The adhesive composition for high-draw lithium battery aluminum-plastic film according to claim 1, characterized in that: The preparation method of the modified epoxy resin comprises the following steps: S41, according to the mass fractions, add phenol, xylene formaldehyde resin and toluene solvent into the reactor and stir until fully dissolved, fill with nitrogen and heat to 160-170°C, add monobutyl tin triisooctanoate and continue to reflux for 2-3h until the water is removed, to obtain modified xylene formaldehyde resin; S42. According to the mass fraction, the reaction temperature is lowered to below 95°C, N'-dimethylurea is added, and the temperature is raised to the reflux temperature. After the reflux becomes clear, tri(2,3-epoxypropyl)isocyanurate and acetone are added to react for 35 hours. After the acetone is removed by rotary evaporation, a modified epoxy resin is obtained.
5. The adhesive composition for high-draw lithium battery aluminum-plastic film according to claim 4, characterized in that: The mass ratio of the phenol, xylene formaldehyde resin, toluene, monobutyltin triisooctanoate, N'-dimethylurea, tri(2,3-epoxypropyl)isocyanurate and acetone is 100:240:500-550:0.1-0.2:0.2-0.3:147:250-270.
6. The adhesive composition for high-draw lithium battery aluminum-plastic film according to claim 1, characterized in that: The preparation method of the castor oil modified polyester polyol comprises the following steps: S61. Add neopentyl glycol and castor oil into a reactor according to their mass fractions, mix and stir, add tetrabutyl titanate under nitrogen protection, raise the temperature to 210° C., maintain the temperature for reaction for 2-3 hours, and obtain product A; S62, according to the mass fraction, cool the product A to 125°C, add adipic acid under nitrogen protection, slowly raise the temperature to 190-200°C, maintain the temperature for 4-6 hours; after the reaction is completed, cool to room temperature to obtain product B; S63. Add triethylamine to product B according to mass fractions, and react at room temperature for 10-20 minutes to obtain castor oil-modified polyester polyol.
7. The adhesive composition for high-draw lithium battery aluminum-plastic film according to claim 6, characterized in that: The mass ratio of the castor oil, neopentyl glycol, tetrabutyl titanate, adipic acid and triethylamine is 90-100:20-23:0.05-0.1:6-8:0.1-0.
3.
8. The adhesive composition for high-draw lithium battery aluminum-plastic film according to claim 1, characterized in that: The coupling agent is composed of dodecyltrimethoxysilane, octyltrimethoxysilane and anilinemethyltriethoxysilane in a mass ratio of 3:2:1-3.
9. The adhesive composition for high-draw lithium battery aluminum-plastic film according to claim 1, characterized in that: The active diluent is butyl glycidyl ether, and the solvent is butanone.
10. A method for preparing an adhesive composition for a high-draw lithium battery aluminum-plastic film according to any one of claims 1 to 9, characterized in that: The following steps are involved: S101, adding one-half of the solvent and active diluent into a reaction kettle according to the mass fraction, heating to 50-55° C. and stirring, adding polyester resin, modified epoxy resin, castor oil-modified polyester polyol and neopentyl glycol to completely dissolve; then adding coupling agent, stirring and aging, adjusting the solid content and then discharging; obtaining a mixture; S102, adding hexamethylene diisocyanate curing agent to the remaining solvent for dilution, stirring evenly, and then adding it to the mixture, stirring evenly, to obtain an adhesive composition for high-draw depth lithium battery aluminum-plastic film.
Citation Information
Patent Citations
Deep-drawing resistant two-component adhesive composition for lithium battery aluminum-plastic film and its preparation method
CN109679567B